Investigating the extent and causes of immigration tendency among medical graduates of Jundishapur university of medical sciences, Ahvaz - Mehdi Torabizadeh; Mohadeseh Hatef; Abdolhossein Shakurnia; Nasrin Khajeali (BMC Medical Education)
Abstract Background The migration of scientific elites is considered one of the serious threats to the health system in the country. This has grown significantly in recent years, and many short-term and long-term consequences are considered for it. This study aimed to investigate the rate and effective causes of migration among general physicians (GPs) of Ahvaz Jundishapur University of Medical Sciences. Methods In this descriptive and analytical study, the study population was the GPs of Jundishapur University of Ahvaz in 2021 and 2022, who were conducted on 235 medical graduates. The tool for measuring the causes of migration was a researcher-made questionnaire consists of 21 items. That was used after determining the validity and reliability by available sampling method. To analyze the data, t, ANOVA, Pearson correlation coefficient and linear regression tests were performed using SPSS version 22 software. Results Out of 225 participants, 51.1% were female and 48 were male. 68% (153) were single and 32% (72 people) were married. Male GPs’ desire to migrate is significantly higher than female (p = 0.040). And the tendency to immigrate was higher among GPs whose fathers had doctorate degrees and higher (p = 0.026). Economic and occupational factors with the highest average (4.32), followed by social and political factors (3.73), the most important factors and the commitment of human resources with an average of (2.74), followed by national and religious affiliation with an average of (2.81) They had the least impact on the tendency to migrate. Conclusion The desire of GPs to migrate is more than average. The desire to migrate among male GPs, doctorate degrees and above, economic and occupational factors with the highest average, followed by social and political factors had the most important influence on the tendency to migrate. It seems that the role of governing institutions in building trust, increasing efficiency And practical response to meet the material and extra-material needs of the country’s GPs and planning in the field of strengthening the pull factors that improve the sense of social belonging is very important. Resolving the immigration issue requires serious, comprehensive, and long-term commitment to the issue of elite management, the completion of structural and legislative concepts, meritocracy, and increasing hope in the academic community. Clinical trial number Not applicable.